A Physiological Perspective on Treadmill and Sit-to-Stand Workstations. (July 2015) - John, Dinesh; Lyden, Kate; Bassett, David R.
Active workstations, such as treadmill and sit-to-stand workstations, enable office employees to break prolonged sitting with bouts of light-intensity walking and/or standing. Compared with sitting, walking and/or standing accumulated during the workday using these workstations will increase muscle contractions, which may influence blood flow, energy expenditure, metabolism, musculoskeletal health, and brain function. Physiological responses when using treadmill and sit-to-stand workstations may vary due to differences in muscle contraction type (dynamic vs. static) and may thus affect cardio-metabolic and musculoskeletal health and brain function in different ways.